SEIZURE SEVERITY AS AN ALTERNATIVE MEASURE OF OUTCOME IN EPILEPSY - Koraliya S. Todorova; Valentina S. Velikova; Ara G. Kaprelyan; Stefan T. Tsekov (Peytchinski Publishing, 2013)
Seizure severity emerges as an important aspect of epilepsy. This is most relevant in refractory patients in whom complete remission of seizures is unlikely and reduced seizure severity may be a significant determinant of psychosocial well-being with a consequent improvement in quality of life (QOL). Thus a valid measure of seizure severity can serve both as an indicator of clinical outcome and as an evaluation tool of the interaction between seizures and the psychosocial complications of epilepsy.After a brief review of the most frequently used scales measuring seizure severity in adults with epilepsy we have explored the relationship between seizure severity and QOL in a set of 103 patients. Two self-evaluation questionnaires were applied: the Seizure Severity Questionnaire (SSQ) and the Quality of Life in Epilepsy Inventory (QOLIE-31). The severity of the coexisting depression, an important confounder in the relationship between seizure severity and QOL, was assessed by the Hamilton Depression Rating Scale (HAMD-17).All domains of the Quality-of-Life in Epilepsy Inventory (QOLIE-31) correlated highly significantly with seizure severity (p≤0.01). The correlation was strong for the Overall score (r=-0.70; p≤0.001) and the Seizure worry domain (r=-0.71; p≤0.001). When the potentially confounding effect of depression was controlled for, the regression of seizure severity with the QOLIE-31 Overall score (P=0.001; R²=0.56) and the Seizure worry domain (P=0.001; R²=0.50) remained significant. These findings indicate that seizure severity is strongly associated with QOL in epilepsy and could be used as an alternative indicator of outcome in clinical research.